Heirs to Byzantium: identity and the Helleno-Romaic dichotomy amongst the Istanbul Greek migrant community in Greece*. (2014) - Halstead, Huw
Abstract : The Istanbul Greek migrant community resident in Greece exists in the space between two homelands and two identities, expressed in the dichotomy between the Hellenic and the Romaic. The migrants exploit this flexibility and ambivalence in Greek identity to contextually navigate a range of social pressures – diaspora, discrimination, alienation, and even financial collapse. At times they pursue assimilation with their host population as the most Hellenic of the Hellenes, whilst at other times they assume a Romaic identity to distinguish themselves from the mainland Greeks. Deploying an identity rooted in Byzantium, the Istanbul Greeks are able to be Greek but more than simply Hellenic.